Effectiveness of treatment for different stages of diabetic retinopathy in type 2 diabetes - A.V. Serdiuk; S.Yu. Mogilevskyy; S.V. Zyablitzev; O.Yu. Denisiuk (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Objectification of the choice of treatment methods based on a comprehensive assessment of their effectiveness depending on the stage of diabetic retinopathy (DR) and biomarkers characterizing the state of the eye, metabolism and other parameters of homeostasis is an urgent modern task of precision medicine. The purpose of the study was to establish the effectiveness of treatment methods in DR of various stages and to determine prognostic indicators of the risk of its rapid progression during 2 years of treatment in the setting of an ophthalmological hospital. Materials and methods. Three hundred and fifty-eight patients (358 eyes) with type 2 diabetes mellitus (T2DM) and DR were examined and divided into the following groups: first one — nonproliferative DR (NPDR, 189 eyes), second one — with preproliferative DR (PPDR; 96 eyes) and the third one — proliferative DR (PDR; 73 eyes). The patients were examined using ophthalmic methods: the central retinal thickness (CRT, μm) and the central retinal volume (CRV, mm3) were determined according to optical coherence tomography data. The analysis of the results was carried out in the EZR v. 1.54 package (Austria), the classification of models — in the Statistica Neural Networks v. 4.0C (StatSoft Inc.). The method of building linear neural network classification models was used to analyze the influence of factor characteristics associated with the risk of DR progression. Results. Rapid progression was noted in 16.9 % of patients with NPDR who received conservative treatment for 2 years, its risk was associated with the value of the CRV (p < 0.001). For conservative and laser treatment, the thresholds for a negative prognosis were found by the value of the CRV (more than 0.285 and 0.180 mm3, respectively). For anti-VEGF therapy and combined treatment, the prognosis of effectiveness was negative. Rapid progression of PPDR was detected in 69.5 % of patients. Its risk was associated with the type of treatment and the size of the CRT, according to which the thresholds of a negative prognosis were established for anti-VEGF therapy and combined treatment (more than 345 and 185 μm, respectively). The prognosis of the effectiveness of laser and surgical treatment in PPDR was positive. Rapid progression of PDR within 2 years was noted in 69.9 % of patients. Its risk was associated with the type of treatment, prothrombin time, and the value of the CRV, which determined the effectiveness of surgical and combined treatment. For anti-VEGF therapy alone, the prognosis of effectiveness was negative. Conclusions. The study conducted made it possible to evaluate the effectiveness of treatment methods in DR of various stages and to establish factors associated with a negative risk of the outcome of two-year treatment.